Humidity effect on dust storm attenuation prediction for 21 GHz microwave links in Sudan - Eltahir, E.I.; Elsheikh, Elfatih A. A.; Babiker, A. Awad; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi; Hassan Abdalla Hashim, Aisha; Saad, Elessaid; Suliman, F.M. (2021)
Dust storms affect the performance of microwave links. Several dust storm attenuation prediction models were proposed by researchers based on theoretical assumptions of either single - particle scattering theorems or numerical methods. The climate conditions and signal variations on microwave link operated at 21 GHz were monitored concurrently in Khartoum, Sudan for one year period. It was observed that dust storms are accompanied with increase of relative humidity and decrease in the received signal. The attenuation predicted by theoretical models and the measured attenuation at 21GHz were compared for a dry and humid case. The predicted attenuations in humid condition are varied significantly and increased 5 times more than dry dust condition. From these results it's obvious that all the theoretical methods are unable to determine the attenuation of microwave propagation in dust storm at 21GHz and it's essential to improve available models by considering the effect of humidity.